Go-to-Market Strategy for a Student-Led Startup Business - Geraga, Alexander George; Comez, Kenn Ivan; Dacanay, Kyli Cursty Lowi; Mondala, Jesus; Recto, Reine Angelo; Tapia, Zyra Ysabel; Pasahol, Jhon Ven Saint (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the Go-to-Market Strategy of a Student-Led Startup Business as perceived by faculty members and entrepreneur students. It aimed to determine how the respondents evaluated the startup’s strategy in terms of market research and customer segmentation, value proposition and product positioning, marketing and promotion strategy, sales and distribution channel, pricing strategy, and customer engagement and retention. The study was anchored on the Input-Process-Output model, where the inputs included related references, respondents, survey results, and problems encountered; the process involved questionnaire formulation, validation, administration, and assessment of GTM components; and the output was a proposed development plan for improving the student-led startup business. The study employed a descriptive survey method using a cross-sectional survey design. Purposive sampling was used to select 100 respondents from Eulogio “Amang” Rodriguez Institute of Science and Technology in Metro Manila, composed of 90 fourth-year entrepreneur students and 10 faculty members. Data were gathered through a validated survey questionnaire using a five-point Likert scale. The data were analyzed using percentage, weighted mean, ranking, and independent samples t-test at the 0.05 level of significance. The findings showed that the Go-to-Market Strategy of the Student-Led Startup Business was generally assessed positively. Market Research and Customer Segmentation obtained a composite mean of 4.228 and was interpreted as Very High Assessment. Value Proposition and Product Positioning obtained 4.129 and was interpreted as High Assessment. Marketing and Promotion Strategy obtained the highest composite mean of 4.240 and was interpreted as Very High Assessment. Sales and Distribution Channel obtained 4.143, Pricing Strategy obtained 4.179, and Customer Engagement and Retention obtained 4.184, all interpreted as High Assessment. The overall grand mean of 4.184 indicated a High Assessment. The independent samples t-test showed that all computed p-values were greater than 0.05, indicating no significant difference between the assessments of faculty members and entrepreneur students. The proposed business plan was developed to improve market research practices, strengthen value proposition, enhance promotional activities, optimize sales and distribution channels, implement competitive pricing strategies, and develop customer engagement programs. The study aligns with SDG 4 on Quality Education by supporting entrepreneurship learning and applied business instruction, SDG 8 on Decent Work and Economic Growth by strengthening student entrepreneurship, and SDG 9 on Industry, Innovation and Infrastructure by encouraging innovation-driven and digitally supported startup practices. Its sustainability impact lies in improving educational, institutional, technological, and socio-economic sustainability by helping student entrepreneurs develop more competitive, customer-centered, and sustainable startup businesses.